Three-dimensional assessment of the ideal insertion angle and position of temporary anchorage devices in the anterior palate: (in a sample of erbil city). - Melav Musa Ibrahim; Omar Fawzi Chawshli (Erbil Dental Journal)
Background and Objectives: Mini-screws may be used in a variety of alveolar bone sites and can withstand loading, allowing for better orthodontic anchoring. The position and placement of mini-screws are determined by the quality and quantity of bone. This study aims to anatomically assess the anterior palate as the insertion site for the orthodontic bone screw. Method: A retrospective study was done by collecting three-dimensional data of the anterior palate for 40 patients with an age range of (20-30 years). The setting of the study was a private Maxillofacial Radiology Center in Erbil City. Measurements at 32 reference points and angulations were done with the help of a Radiologist to determine the ideal insertion point and angulation for TADs in the anterior palate. Results: The thickness of the anterior palate was found to differ significantly (p=0.00) among the 32 points studied, including 20 points at a zero angle to a vector perpendicular to the curve of the palate and three additional angles at 10, 20, and 30 degrees to a vector perpendicular to the curve of the palate. The thickest point in the anterior palate was 6mm away from the midline at the contact point between canine and first premolar on both the left and right sides. The reference point with the least thickness was determined to be 3mm to 6mm distant from the midline at the intersection with the center of the second premolar on the right and left. Conclusion: In conclusion, the thickness of the palatal hard tissue decreased from the anterior to the posterior.